Penerapan Manajemen Layanan Informasi dalam Bimbingan dan Konseling - Bakhrudin All Habsy; Lisa Septiani; Tharifah Haibaty Kurniawan; Dhiyah Khofifah; Disma Nadya Shakila; Alfi Kamelia Mubarok; Syafa’atun Nur Fajariyah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Information services are a form of service in guidance and counseling that is very important for students. Information services are information delivery activities as a systematic effort by counseling teachers to help students in the process of understanding, making decisions, and supporting their development towards independence. The method used in this research is a qualitative method with a type of literature study, namely collecting relevant and valid data and sources related to the research topic being studied. Then the data will be analyzed using the description analysis method. This research is expected to add insight, especially for counseling teachers related to information service management. The results of this study include: (1) Definition of information services, (2) Types and sources of information, (3) Mechanisms for presenting information..